Methodology for determining the nature and dynamics of wear of plunger pair parts - Viunyk, Olha; В'юник, Ольга Володимирівна; Kovshar, A. (Запоріжжя: ТДАТУ, 2025)
The work is part of a series of articles devoted to increasing the durability of plunger pairs of axial piston pumps. The purpose of the research is to increase the durability of mobile machines and improve the operational characteristics of axial piston pumps by minimizing power losses based on modeling of tribological processes in plunger pairs.
Keywords: plunger pair parts; mobile machines